1996
DOI: 10.3109/00365529609006408
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glutamine Content in Colonic Polyps

Abstract: Adenomatous polyps might behave as a glutamine trap, channeling glutamine to protein and nucleic acid synthesis. These changes in glutamine catabolism could play a role in colonic neoplasia pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Higher glutaminase activities were found in human intestine than in colon tissues (38). In colonic polyps, GLN content and glutaminase activities were lower than in normal-paired tissues (39). Our results suggested that the transcriptional levels of each isoform may be regulated differently in the presence of GLN.…”
Section: Discussionmentioning
confidence: 56%
“…Higher glutaminase activities were found in human intestine than in colon tissues (38). In colonic polyps, GLN content and glutaminase activities were lower than in normal-paired tissues (39). Our results suggested that the transcriptional levels of each isoform may be regulated differently in the presence of GLN.…”
Section: Discussionmentioning
confidence: 56%
“…It has two nitrogen groups in side chains that act as the most important transporter of circulating nitrogen. [ 14 20 ] Therefore, its supplementation affects nitrogen balance and increase retain of nitrogen, because of the quantity of nitrogen provided by Gln. [ 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 45 ] It has been illustrated that Gln consumption increases in tumor tissues and consequently decreases its concentration. [ 14 ] Hence, it is possible that Gln feeding can help to high gastrointestinal tract tumor cell turnover that it may lead to more growth of these cells. [ 52 53 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation